2022
DOI: 10.1021/acs.iecr.2c00937
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Refrigerant Separation Using Extractive Distillation with Ionic Liquids

Abstract: Hydrofluorocarbon refrigerants are being phased out over the next two decades due to concerns about high global warming potential. In order to separate refrigerant mixtures that form azeotropes, new technologies will be required. Currently, fractional distillation is unable to efficiently separate azeotropic refrigerant mixtures. Extractive distillation using an ionic liquid as the entrainer offers a solution. Vapor–liquid equilibria data for refrigerants difluoromethane (HFC-32), pentafluoroethane (HFC-125), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 130 publications
0
48
0
Order By: Relevance
“…One technology that is currently being investigated for the separation of complex refrigerant mixtures is extractive distillation with ionic liquids (ILs) as entrainers. ILs show promise as entrainers for this separation due to their unique properties including negligible vapor pressure and dissolution of different gases. Significant work has been done to investigate equilibrium and thermophysical properties of refrigerants with a variety of neat ILs. …”
Section: Introductionmentioning
confidence: 99%
“…One technology that is currently being investigated for the separation of complex refrigerant mixtures is extractive distillation with ionic liquids (ILs) as entrainers. ILs show promise as entrainers for this separation due to their unique properties including negligible vapor pressure and dissolution of different gases. Significant work has been done to investigate equilibrium and thermophysical properties of refrigerants with a variety of neat ILs. …”
Section: Introductionmentioning
confidence: 99%
“…As such, technologies to recycle these HFCs are developing quickly. For example, recent work demonstrates how ionic liquids (ILs) can facilitate HFC separation. Other works have used machine learning to search for new refrigerants and estimate HFC solubility in ILs. , However, all HFC separation endeavors require the often limited knowledge of the thermophysical properties of these HFC mixtures. , Computer-aided molecular design of HFC separations ,, has shown promise to accelerate the development of novel processes to meet the required goals. Accurate vapor–liquid equilibrium (VLE) data of HFC mixtures are desired, as is a microscopic understanding of the underlying physics that governs their physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed solutions for the separation of HFCs and other refrigerants include ionic liquids as entrainers in extractive distillation and selective adsorption using porous materials such as activated carbons, zeolites, and metal–organic frameworks. Membrane technology has also been considered in the literature for HFC separation, specifically in regard to HFC-32, HFC-125, HFC-134a, and HFO-1234yf. For example, Pardo et al reported the use of poly(ether- block -amide) (PEBA) membranes for the separation of HFC mixtures containing the refrigerants HFC-32, HFC-134a, and HFO-1234yf (CH 2 CFCF 3 ) .…”
Section: Introductionmentioning
confidence: 99%